External iliac artery Doppler assessment in the prediction of adverse pregnancy outcomes. (17th December 2018) - De Paco-Matallana, Catalina; Ventura, Walter; Prieto-Sánchez, Maria Teresa; Pertegal, Miriam; Macizo, Maria Isabel; Peñalver, Carolina; Arteaga, Alicia; Hernández, Isabel; Delgado, Juan Luis
Abstract: Purpose: The purpose of this study is to investigate the potential role of the mean external iliac artery pulsatility index (EIA-PI) as a predictor of adverse obstetric outcomes such as preeclampsia, gestational hypertension and small for gestational age (SGA). Methods: In women attending for first trimester screening at 11 + 0–13 + 6 weeks of gestation, we recorded maternal characteristics and measured EIA mean PI and uterine artery mean PI. We compared EIA mean PI in those that developed preeclampsia ( n = 84), gestational hypertension ( n = 50) or small for gestational age ( n = 444) with those unaffected ( n = 3736). Regression analysis was used to first determine which of the factors among the maternal variables were significant predictors of EIA mean PI in the unaffected group and, second, to predict adverse pregnancy outcomes. Results: In the unaffected group, EIA mean PI increased with maternal age and decreased with mean blood pressure. Additionally, EIA mean PI was lower in cigarette smokers. Compared with the unaffected group, EIA mean PI was significantly lower in women who develop gestational hypertension or SGA below third centile. Conclusion: EIA mean PI in the first trimester is decreased in women who develop gestational hypertension and in those complicated by SGA below third centile. More studies are needed to confirm these findings.